2017
DOI: 10.1007/s10499-017-0210-6
|View full text |Cite
|
Sign up to set email alerts
|

Dietary β-glucans and mannanoligosaccharides improve growth performance and intestinal morphology of juvenile pacu Piaractus mesopotamicus (Holmberg, 1887)

Abstract: The objective of this study was to evaluate the effect of increased levels (0.0, 0.1, 0.2, 0.4, and 0.8%) of a combination of β-glucans and mannanoligosaccharides (MOS) in isonitrogenous (23% of digestible protein) and isoenergetic (13.38 MJ of digestible energy kg-1) pacu diets, corresponding to five treatments and four replicates. A 30-day feeding trial was conducted to assess the effects on growth performance, hematological parameters, and intestinal morphology. Fish (n = 160, 30.92 ± 0.46 g) were distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 35 publications
2
17
1
Order By: Relevance
“…On one hand had no effect on hematocrit, MCHC, MCV, respiratory burst of leukocytes, total protein, albumin and number of eosinophils. Similarly, P. mesopotamicus supplemented with a combination of 1-8% of β-glucan and mannanoligosaccharides for 30 days, did not change the number of erythrocytes, hematocrit, hemoglobin, MCHC, VCM, and total plasma protein levels [9]. In H. huso supplemented with 1-2% of S. cerevisiae in the diet, for 42 days, no changes in plasma levels of total proteins, glucose, erythrocytes, hematocrit, hemoglobin, MCHC, MCV and Table 3 Plasma biochemical parameters and blood immune parameters of Arapaima gigas, after 30 days feeding the experimental diets.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…On one hand had no effect on hematocrit, MCHC, MCV, respiratory burst of leukocytes, total protein, albumin and number of eosinophils. Similarly, P. mesopotamicus supplemented with a combination of 1-8% of β-glucan and mannanoligosaccharides for 30 days, did not change the number of erythrocytes, hematocrit, hemoglobin, MCHC, VCM, and total plasma protein levels [9]. In H. huso supplemented with 1-2% of S. cerevisiae in the diet, for 42 days, no changes in plasma levels of total proteins, glucose, erythrocytes, hematocrit, hemoglobin, MCHC, MCV and Table 3 Plasma biochemical parameters and blood immune parameters of Arapaima gigas, after 30 days feeding the experimental diets.…”
Section: Discussionmentioning
confidence: 85%
“…Supplementation with 0.1% of S. cerevisiae in the Table 2 Growth performance parameters of Arapaima gigas fed the experimental diets for 30 days. diet of O. niloticus [23] and 2% in the diet of Huso huso [24], as well as 2% of β-glucan combined with mannanoligosaccharides in the diet of Piaractus mesopotamicus [9] improved fish growth performances. The previous studies indicated that S. cerevisiae-based products were efficient in promoting fish growth and potentially viable for aquaculture use from the production viewpoint.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Fish fed 2,000 mg kg -1 L-carnitine had taller and less-thick villi (Table and Figure 3), which represents an adaptation of the tissue to the food, suggesting an improvement in the surface area for the absorption of nutrients (Hisano et al, 2018). In pacu, the intestinethe main organ for nutrient digestion and absorption in fish -is medium sized and lined by folds, which are distributed longitudinally, being wider and more complex in the median portion, where there is a greater nutrient absorption (Corrêa, 2016).…”
Section: Variablementioning
confidence: 99%